The DIAB.&TE.S. project: how patients perceive diabetes and diabetes therapy - “DIAB.&TE.S Project”, Study Group (Acta Biomedica Atenei Parmensis, 2004)
Assessment of quality of life (QoL) in diabetic patients is increasingly retained as a crucial parameter to take into account before concluding on the efficacy of new therapies. Indeed, the trend is to adopt treatments providing a genuine clinical benefit associated with a positive impact on QoL. In this context, DIAB.&TE.S Project aimed at analyzing patient’s perception of psychological well-being, quality of treatment and their correlation with glyco-metabolic values control. A total of 1918 diabetic patients, mostly from southern Italy, were enrolled in this observational study. DIAB.&TE.S included a wide range of patients taking insulin monotherapy, OHA (oral hypoglycemic agents) monotherapy or combined therapy (insulin + OHA). Internationally recognized instruments such as the Well-Being Questionnaire (WBQ) and Diabetes Treatment Satisfaction Questionnaire (DTSQ) were used to assess general well-being and diabetes treatment satisfaction. Combined therapy was not highly efficient in achieving both glycemic and quality of life goals when compared to insulin or OHA monotherapies. Oral monotherapy produced better results if compared to insulin treatment, as demonstrated by DTSQ and WBQ scores. However, among the insulin treated subjects, higher scores were reached in patients using advanced devices to administrate insulin. Finally, a correlation between questionnaires outcomes and metabolic control in patients could be established. Our findings support the idea that in diabetes therapy, integration of clinical and psychosocial cares could be helpful in both identifying subjects that need a treatment re-examination and improving patient’s quality of life. In addition, this survey by its magnitude provides an overview of diabetes management in Italy and contributes to set up an accurate profile of diabetic people in this part of Europe.